Chemo-enzymatic modification of poly-N-acetyllactosamine (LacNAc) oligomers and N,N-diacetyllactosamine (LacDiNAc) based on galactose oxidase treatment - Kupper, Christiane E.; Rosencrantz, Ruben R.; Henßen, Birgit; Pelantová, Helena; Thönes, Stephan; Drozdová, Anna; Křen, Vladimir; Elling, Lothar (Beilstein Journal of Organic Chemistry, 2012)
The importance of glycans in biological systems is highlighted by their various functions in physiological and pathological processes. Many glycan epitopes on glycoproteins and glycolipids are based on N-acetyllactosamine units (LacNAc; Galβ1,4GlcNAc) and often present on extended poly-LacNAc glycans ([Galβ1,4GlcNAc]n). Poly-LacNAc itself has been identified as a binding motif of galectins, an important class of lectins with functions in immune response and tumorigenesis. Therefore, the synthesis of natural and modified poly-LacNAc glycans is of specific interest for binding studies with galectins as well as for studies of their possible therapeutic applications. We present the oxidation by galactose oxidase and subsequent chemical or enzymatic modification of terminal galactose and N-acetylgalactosamine residues of poly-N-acetyllactosamine (poly-LacNAc) oligomers and N,N-diacetyllactosamine (LacDiNAc) by galactose oxidase. Product formation starting from different poly-LacNAc oligomers was characterised and optimised regarding formation of the C6-aldo product. Further modification of the aldehyde containing glycans, either by chemical conversion or enzymatic elongation, was established. Base-catalysed β-elimination, coupling of biotin–hydrazide with subsequent reduction to the corresponding hydrazine linkage, and coupling by reductive amination to an amino-functionalised poly-LacNAc oligomer were performed and the products characterised by LC–MS and NMR analysis. Remarkably, elongation of terminally oxidised poly-LacNAc glycans by β3GlcNAc- and β4Gal-transferase was also successful. In this way, a set of novel, modified poly-LacNAc oligomers containing terminally and/or internally modified galactose residues were obtained, which can be used for binding studies and various other applications.
Keywords: chemo-enzymatic synthesis; galactose oxidase; glycosyltransferase; LacDiNAc; poly-N-acetyllactosamine